From a/topia to topia: Towards a gendered right to the city for migrant volunteers in London. (June 2018) - Vacchelli, Elena; Peyrefitte, Magali
Abstract: The paper makes use of an un-orthodox Lefebvrian formulation of the 'right to the city' as it adds the gender dimension which was absent from Lefebvre's work. The lens of 'gendered right to the city' (Doderer, 2003; Fenster, 2005; Vacchelli, 2014) is used in order to understand the experiences of volunteers working in the women's community and voluntary sector in London. We look specifically at the role of migrant organisations both as places of co-option of migrant labour, as places that enable the integration of migrants and make their participation in the urban fabrics possible, and as places that are appropriated by migrant volunteers in London as a means of enacting active citizenship. London's governance, policy discourses and practices seek to impose a top-down idea of civic participation. In this vision, the role of migrant groups and organisations can only be valued in the context of an active civil society, able to replace the vacuum left by the progressive erosion of the welfare state, leading to a crisis of social reproduction. Lefebvre's theoretical framework of 'space appropriation' serves as a way to explore these questions and we propose a further spatial reading which is specific to a gendered right to the city, i.e. the shift from a/topia (not having a space or being denied access to public spaces broadly conceived) to topia . We speculate on what this newly found space looks like and what is its potential for the subversion of top-down policy discourses on civic participation in the neoliberal city. Highlights: An analysis of migrant women's volunteer work in London is proposed Their position of invisibility makes it difficult to achieve social mobility and participate in the public sphere as citizens Policy discourses impose top-down model of active citizenship contrarily to experiences of migrant women volunteers We understand topia as a public space allowing volunteers to participate through solidarity practices of mutual support Civic participation from below enacts resistance through solidarity i.e. space appropriation in terms of the right to the city